Evaluation of DNA versus collagen perception in scientific articles examining cancer and radiation therapy: implication for collagen based approaches - Karaman, Şule; Karaçay, Özge; Dizdar, Yavuz (The European Research Journal, 2023)
Objectives: Although radiation therapy has been used for more than a hundred years, its definitive mechanism of action is not known. Many studies indicate that radiation induces free radicals which damage DNA. However, irradiation should also affect the collagen connective tissue matrix. This database analysis aims to determine the extent of DNA versus collagen perception in scientific papers. Methods: Journals indexed in PubMed were searched on March 3, 2022, using the medical keywords "cancer", "radiation therapy", "radiation therapy AND damage," radiation therapy AND mechanism AND damage, "radiation therapy AND clinical". The number of items found for each search was proportioned in terms of “DNA versus collagen” and the ratio was accepted as the perception shift coefficient. Results: Results were tested with the p-value analysis to calculate the difference between the two proportions in both search items. Based on the main rule under the assumption that “all cells have DNA and all cells live in the collagen matrix”. In the p1-p2 analysis of the data, a significant (p < 0.001) difference was obtained for all dichotomy scans. Conclusions: This data analysis supports the argument that both cancer and radiation therapy perception is DNA-based rather than collagen, since the synthesis and degradation process of very slow; it is not possible to observe it in short-term studies. The effects of irradiation should be further analyzed in this manner for purpose of collagen matrix interaction.